Embodied aesthetics : proceedings of the 1st International Conference on Aesthetics and the Embodied Mind, 26th-28th August 2013 - Scarinzi, Alfonsina (Philosophy of history and culture ;, 2014)
The volume presents the results of the 1st International Conference on Aesthetics and the Embodied Mind. It discusses from different points of view the role of embodiment in the reevaluation of aesthetics as a process of bodily mediated meaning-making.